Building Bigness: Reputation, Prominence, and Social Capital in Rural South India. Issue 3 (15th July 2018) - Power, Eleanor A.; Ready, Elspeth
ABSTRACT: Anthropologists have long been concerned with how reputations help people gain the support of others. Here, we study the support ties among adult residents of two Tamil villages, asking how reputational standing in each village mediates access to social support. We find that a reputation for influence has the weakest effect on support ties with others, while a reputation for generosity has the strongest. Further, a reputation for influence is not associated with greater connections to people of "high position" outside the village. Given the weak effects of a reputation for influence, we turn to a network measure of social capital, weighted PageRank centrality. While persons who are recognized as influential often also have an influential network position, there are many others who have similarly high centrality—including, notably, many women. Consequently, we suggest that much of the anthropological evidence for the benefits of prominence may actually reflect the returns to greater social capital and that both may be shaped in large part by acts of generosity and mutual support. By studying social capital, we can achieve a more complete accounting of the many different social strategies employed by all persons, not simply the few who achieve prominence. [ reputation, social capital, network analysis, prominence, India ]